Ambient observations of hygroscopic growth factor and f(RH) below 1: Case studies from surface and airborne measurements. Issue 22 (23rd November 2016) - Shingler, Taylor; Sorooshian, Armin; Ortega, Amber; Crosbie, Ewan; Wonaschütz, Anna; Perring, Anne E.; Beyersdorf, Andreas; Ziemba, Luke; Jimenez, Jose L.; Campuzano‐Jost, Pedro; Mikoviny, Tomas; Wisthaler, Armin; et al.
Abstract: This study reports a detailed set of ambient observations of optical/physical shrinking of particles from exposure to water vapor with consistency across different instruments and regions. Data have been utilized from (i) a shipboard humidified tandem differential mobility analyzer during the Eastern Pacific Emitted Aerosol Cloud Experiment in 2011, (ii) multiple instruments on the NASA DC‐8 research aircraft during the Studies of Emissions, Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys in 2013, and (iii) the Differential Aerosol Sizing and Hygroscopicity Spectrometer Probe during ambient measurements in Tucson, Arizona, during summer 2014 and winter 2015. Hygroscopic growth factor (ratio of humidified‐to‐dry diameter, GF =  D p, wet /D p, dry ) and f (RH) (ratio of humidified‐to‐dry scattering coefficients) values below 1 were observed across the range of relative humidity (RH) investigated (75–95%). A commonality of observations of GF and f (RH) below 1 in these experiments was the presence of particles enriched with carbonaceous matter, especially from biomass burning. Evidence of externally mixed aerosol, and thus multiple GFs with at least one GF < 1, was observed concurrently with f (RH) < 1 during smoke periods. Possible mechanisms responsible for observed shrinkage are discussed and include particle restructuring, volatilization effects, and refractive index modifications due to aqueous processing resulting in optical size modification. To further investigate ambient observations of GFs and f (RH) values less than 1, it is recommended to add an optional prehumidification bypass module to hygroscopicity instruments, to preemptively collapse particles prior to controlled RH measurements. Key Points: Observations are reported for growth factor (GF) and f(RH) values below 1 in multiple regions using three instruments GF and f(RH) values less than 1 are observed in biomass burning plumes, organic‐rich particles, and wintertime in an urban area f(RH) increases as a function of effective particle density with the majority of values below 1 coincident with density <1.2 g cm −3